An internet-based information system for the sport scientific theory of selected sports disciplines - Baca, A.; Eder, C. (International Journal of Computer Science in Sport, 2003)
An information system is developed to transmit scientific basics of four selected sport disciplines using internet and multimedia technology. The aim of the project is to arouse the interest in studying theoretical sport scientific concepts more intensively and to obtain a more rapid understanding for complex connections. We expect to improve the interdisciplinary understanding in sport science both in research and education and to achieve a more economic and effective education. Four modules are developed. The online availability of the modules shall enable users to earn, refresh or deepen their knowledge, independent of time and place. Computer animations, video sequences (e.g. to control the ability to diagnose anomalies in motion performance or to specify the cognitive representation of movements) and simulations (e.g. to illustrate the influence of different parameters such as that of the effect of the ball rotation to the trajectory in tennis) are included into the modules in order to achieve a high degree of interactivity. The first module (Alpine skiing) is available since September 2002. Evaluation results comply with the expectations.